Transforming Amicus Curiae Through an Experimental Jurisprudence Framework in Judicial Decision-Making - Susilo, Erwin; Sujatmiko, Bagus; Arifin, Zaenal (JURNAL USM LAW REVIEW, 2025)
This study examines the contemporary role of amicus curiae in strengthening judicial reasoning through the integration of the Experimental Jurisprudence (X-Jur) framework within the Indonesian legal system. The research addresses the absence of explicit regulations governing amicus curiae despite its increasing use in high-profile cases, creating inconsistencies in judicial treatment and undermining normative clarity. Using a normative legal method complemented by statutory, conceptual, comparative, and case approaches, this study analyzes the doctrinal position of amicus curiae and evaluates its potential as an epistemic instrument that enriches judicial deliberations with empirical, psychological, and social perspectives. The findings demonstrate that amicus curiae provides valuable epistemic input that enhances judicial reflection; however, its current acceptance remains discretionary and fragmented due to the lack of procedural guidelines. The integration of X-Jur reveals a strong empirical connection between public perceptions of justice and judicial reasoning, offering a data-driven foundation for improving the legitimacy and social responsiveness of court decisions. The novelty of this research lies in conceptualizing amicus curiae as a methodological bridge between normative doctrine and empirical cognition, and in proposing a regulatory model—through a Supreme Court Regulation—that institutionalizes amicus curiae as a formal mechanism within Indonesia’s civil law tradition. This framework is essential for strengthening transparency, judicial reflectiveness, and the pursuit of substantive justice in modern adjudication.